Development of Mechanically Alloyed and Sintered W-1 wt.% Ni Matrix Composites Reinforced with TiB2 - Agaogullari, Duygu; Balci, Özge; Demirkan, Ö. Utku; Gokce, Hasan; Genç, Aziz; Öveçoğlu, M. Lütfi; Duman, Ismail (Trans Tech Publications, Ltd., 2012)
Due to improve the physical and mechanical properties of Ni activated W compacts, TiB2 was added to the W-Ni matrix as reinforcing agent. W-Ni matrix composites were fabricated by using a combined method of mechanical alloying (MA), cold pressing and activated sintering. The amount of activated sintering aid (Ni) was kept constant as 1 wt.%. The effects of TiB2 content and mechanical alloying duration on the physical, microstructural and mechanical properties of activated sintered W-Ni compacts were investigated. The results showed that TiB2 particles have a significant effect on the density and microhardness values of the sintered samples. After MA and sintering, formation of W2B and NiTi intermetallic compounds were observed because of the decomposition of TiB2. The relative density value of 91.21 % and microhardness value of 4.08±0.28 GPa of W-1 wt.% Ni samples respectively increased to 94.88 % and 5.64±0.28 GPa with the addition of 2 wt.% TiB2.